Modelling educational games through multi-domain framework in light of game play - Ahmad, M. (Institute of Electrical and Electronics Engineers Inc., 2015)
Game-based learning systems have been proven to provide a highly positive influence with learning industry over the past decade. The challenge occurs when the game developers have to model and develop an effective educational game to understand the depth and relationships between game play (rules and regulations), game environment, learning theories, and the learner's achievement to achieve the objective of subject content embedded in the educational game. Modelling in terms of software engineering for educational games can provide a wider aspect for the game developers. Thus, the authors have proposed a multi-domain framework with extracted implicit relationships through a systematic literature review. These relationships are verified through qualitative interviews with eight (8) game-based learning experts to validate the relationships. This paper presents eleven (11) implicit relationships based on game play domain and discusses their relevancy with game environment, learning theories, and subject-matter (learners, teachers) by applying interpretive hermeneutic approach of qualitative study. Consequently, this paper concludes eleven (11) explicit relationships for game developers to reflect upon during the modelling and developing process of educational games. Â© 2015 IEEE.